Atypical Primary Central Nervous System Post‑Transplant Lymphoproliferative Disorder - Pimenta, Gonçalo (2025)
Post‑transplant lymphoproliferative disorder (PTLD) is a serious complication following kidney transplantation, with Epstein‑Barr virus (EBV) infection being a major risk factor. Central nervous system (CNS) involvement occurs in 5%‑30% of cases, but primary CNS‑PTLD is rare and has a poor prognosis. We report two cases of primary CNS‑PTLD in kidney transplant recipients with atypical presentation. The first case involved a 42‑year‑old female who presented with vertigo 22 years post‑transplant. The second case was a 70‑year‑old male who exhibited abnormal gait 2 years after transplantation. They were initially misdiagnosed, respectively, as vestibular neuritis and stroke. Imaging studies revealed an isolated cerebellar lesion in both cases; diffuse large B‑cell lymphoma was unveiled on the biopsies. The first case was EBV‑related and its management included immunosuppression reduction, surgical resection, and radiotherapy. Both patients ultimately died from infectious complications. These cases highlight the diagnostic challenges and poor out‑comes associated with primary CNS‑PTLD, even with treatment. The variable latency periods, atypical focal cerebellar involvement, and differing EBV status underscore the heterogeneity of this rare entity. Further research is needed to establish optimal diagnostic and treatment protocols for primary CNS‑PTLD in kidney transplant recipients.